Vertical angles are equal to each other:
∠2 = ∠3
5 + 4y = 6y - 25
→ 30 = 2y
→ 15 = y
∠2 = 5 + 4y = 5 + 4(15) = 5 + 60 = 65
linear pairs equal 180:
∠1 + ∠2 = 180
→ ∠1 + 65 = 180
→ ∠1 = 115
Ur gonna have to pick an equation and solve for a variable.
2x - 2y = 6
2x = 2y + 6 ...divide everything by 2 because u want x by itself
x = y + 3
now we sub y + 3 in for x in the other equation
14x - 2y = 78
14(y + 3) - 2y = 78...distribute thru the parenthesis
14y + 42 - 2y = 78...subtract 42 from both sides, cancelling the 42 on the left
-42 -42
-----------------------
14y - 2y = 36 ...simplify
12y = 36...divide by 12 on both sides, cancelling out the 12 on the left
y = 36/12
y = 3
now , we already know that x = y + 3...and we know y = 3...so sub in 3 for y and solve for x
x = y + 3
x = 3 + 3
x = 6
solution is (6,3)
it is always a good idea to check ur answer by subbing it into one or both of the equations to see if it is correct
2x - 2y = 6......(6,3)...x = 6 and y = 3
2(6) - 2(3) = 6
12 - 6 = 6
6 = 6 (correct)
so yes, ur solution is (6,3)
Step 1. Type it into a Google search box or calculator. (You need to use a calculator anyway.) The result is
3177 4/9.
If you're doing this according to the Order of Operations, you do the multiplication and division left to right. This means the first calculation you do is
255/6 = 42.5
Next, you multiply by 672
42.5*672 = 28560
Then divide by 9
28560/9 = 3173 3/9
You continue by doing the division
37/9 = 4 1/9
And finish by adding the two results
3173 3/9 + 4 1/9 =
3174 4/9_____
If you're doing this by hand, you can recognize the first term as the product of two fractions, so is the product of numerators divided by the product of denominators.
(255*672)/(6*9)
Using your knowledge of divisibility rules, you can do the division 672/6 to simplify this to
(255*112)/9
Now, the first term and the second term have the same denominator, so you can add the numerators before you do the division.
(255*112 + 37)/9 = (28560 + 37)/9 = 28597/9
You end up having to do only two simple divisions, rather than 3 of them.
28597/9 = 3177 4/9
What is the third term of the sequence defined by the recursive rule f(1)=3 f(n)=f(n-1)+4
Need f(2):
f(2)=f(2-1)+4
f(2)=f(1)+4
f(2)=(3)+4=7
FIND f(3):
f(3)=f(3-1)+4
f(3)=f(2)+4
f(3)=(7)+4
f(3)=11
Answer:
Step-by-step explanation:
Its correct corrdenates are -8, 1 and 5, -3